2020
DOI: 10.20944/preprints202012.0806.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Active Surveillance in the Management of Ductal Carcinoma in Situ: The Radiologist’s Point of View

Abstract: (1) Background: Considering highly selected patients with ductal carcinoma in situ (DCIS), active surveillance is a valid alternative to surgery. Our study is aimed at showing the reliability of post-biopsy complete lesion removal, documented by mammogram, as additional criterion to select these patients. (2) Methods: 2173 Vacuum Assisted Breast Biopsies (VABB) documented as DCIS have been reviewed. Surgery has been performed in all cases. We retrospectively collected the reports of post-VABB complete lesion r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…They concluded that the rate of upgrading is low enough to recommend AS instead of surgical removal. Moreover, they included all grades of DCIS, which means this ratio may be less if HG-DCIS cases were excluded [47].…”
Section: Upgrading From Ductal Carcinoma In Situ To Invasive Carcinomamentioning
confidence: 99%
“…They concluded that the rate of upgrading is low enough to recommend AS instead of surgical removal. Moreover, they included all grades of DCIS, which means this ratio may be less if HG-DCIS cases were excluded [47].…”
Section: Upgrading From Ductal Carcinoma In Situ To Invasive Carcinomamentioning
confidence: 99%